2018
DOI: 10.1038/s41467-018-06567-6
|View full text |Cite
|
Sign up to set email alerts
|

Copy number load predicts outcome of metastatic colorectal cancer patients receiving bevacizumab combination therapy

Abstract: Increased copy number alterations (CNAs) indicative of chromosomal instability (CIN) have been associated with poor cancer outcome. Here, we study CNAs as potential biomarkers of bevacizumab (BVZ) response in metastatic colorectal cancer (mCRC). We cluster 409 mCRCs in three subclusters characterized by different degrees of CIN. Tumors belonging to intermediate-to-high instability clusters have improved outcome following chemotherapy plus BVZ versus chemotherapy alone. In contrast, low instability tumors, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 56 publications
5
77
1
Order By: Relevance
“…There have been many studies of gene copy number changes in colorectal tumors; 68 these have also been used to create a CRC classification system, based on chromosome instability. 69 . Copy number load was initially studied as a potential biomarker of response to bevacizumab in patients with metastatic CRC.…”
Section: Chromosome Instability and The Tmementioning
confidence: 99%
See 2 more Smart Citations
“…There have been many studies of gene copy number changes in colorectal tumors; 68 these have also been used to create a CRC classification system, based on chromosome instability. 69 . Copy number load was initially studied as a potential biomarker of response to bevacizumab in patients with metastatic CRC.…”
Section: Chromosome Instability and The Tmementioning
confidence: 99%
“…Resistance of tumor cells to drugs (initial or acquired during treatment) poses an constant challenge 156 , and strategies are needed to determine which tumors are most likely to respond to which therapies. Genomic 50,69,[157][158][159][160][161][162][163] and other classes of biomarkers of response have been proposed, 164 but there are no markers that can be used to predict response to anti-angiogenic agents.…”
Section: Biomarkers Of Response To Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The C3 subtype is closely related to the CMS4 type (mesenchymal type). For the characteristics of the CMS4 type, tumor matrix infiltrating epithelial cells, tumor-associated fibroblasts (CAFs) and innate immune cells produce more inflammatory factors [24], which may be the reason for the strong immune activity of the C3 subtype. Most of the 13 types of immune metagene are highly expressed in the C3 subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, these data suggest that CIN, or more likely, the level of CIN, may confer sensitivity or resistance to specific anti-neoplastic drugs. Researchers have also shown that CIN can predict which patients are most likely to benefit from specific treatments, such as bevacizumab (an anti-angiogenic monoclonal antibody targeting vascular endothelial growth factor A [VEGF-A]), a key drug used in the treatment of colorectal and lung cancers [125]. Based on these collective observations, the authors suggest that the presence and level of CIN may be a useful tool that could assist oncologists in stratifying patient cohorts to distinguish those who will benefit from a given treatment from those who will not.…”
Section: Cin and Cancer Prognosismentioning
confidence: 99%